Penguatan Literasi sebagai upaya preventif terhadap Radikalisme-Ekstremisme Beragama di Pondok Pesantren Assalaam Manado - Abdullah Botma; Abdurrahman Wahid Abdullah (Jurnal Ilmiah Iqra', 2022)
Strengthening Literacy as a preventive effort against Radicalism-Religious Extremism at the Assalaam Islamic Boarding School Manado. The spread of extremist ideologies is often linked to religious institutions, including madrasahs and boarding houses. Its message has long been known as a moderate, tolerant religious institution known as "Rahmatan Lil Alamin" (Blessing for everything in this world). The boarding house of Assalam Manado is one of the boarding houses that hopefully can afford preventive measures to ward off the spread of radicalism and religious extremism. This research is a qualitative study technique of data collection through observation and documentation. Research indicates that the efforts of manado's boarding house to counter radicalism have been mainly made through media and literacy. Moreover, efforts made by cultivating the spirit of ukhuwah by working together; Building social coordination and relationships among other elements of leaders, employees, teachers, parents/guardians of student, society, and student; activating student extracurricular; performing routine learning of Kitab for a student.